Participação da proteinase CMS2MS3 na atividade antimetastática de fração do látex de Vasconcellea cundinamarcensis: efeitos sobre a adesão e morte celular - Dalton Dittz Junior (2015)
Our research group has demonstrated that proteolytic fractions P1G10 and CMS2 (derived from P1G10) of Vasconcellea cundinamarcensis latex display antitumor and antimetastatic activity on murine melanoma as demonstrated by reduction in cell adhesion, migration, and induction of apoptosis. The CMS2 was further resolved into five proteases (CMS2MS1-5) when chromatographed on Mono-S Sepharose resin(FPLC). These five proteases were analyzed for their ability to promote cell adhesion changes and death effects seen earlier in less purified fractions, by using a murine metastatic melanoma cell line (B16F10). Among the five analyzed proteases, CMS2MS3 showed the lowest CC-50 (7.81 g/mL) compared to others (34.5 to 303.5 g/mL). Each protease reduced B16F10 adhesion on polystyrene plates, particularly CMS2MS3 at 10 - 50 g/mL. This protease also promoted a reduction in the B16F10 cell adhesion to extracellular matrix components, especially towardsvitronectin and laminin, after treatment with 10 g/mL for 2, 4, 8 or 24 h. The level of 4, 5 and 1 subunits of integrin was reduced when cells were exposed to 10 g/mL CMS2MS3 at each interval analyzed demonstrating that this effect contributes, at least partially, with the loss of adhesion. The number of vinculin/cell reduced 65 85% after 2 h exposure to CMS2MS3, showing that focal adhesion may be linked tothat integrin composed of subunits 4, 5 and 1. After 2 24 h exposure to 50 g/mL CMS2MS3, sub-diploid DNA was increased. However, in lower concentration (10 ug/mL) CMS2MS3 induced a reduction in intracellular levels of pro-caspases 3 and 9 from 2h of exposure of cells, suggesting that cell death ensues apoptosis and loss of cell adhesion. A rapid increase in nuclear and mitochondrial calcium was observedafter B16F10 exposure to CMS2MS3 10 g/mL and this may be related to the release of cytochrome c and activation of apoptosis. Thus, CMS2MS3 showed the strongest cytotoxic effect and the ability to reduce cell adhesion, mediated by 4, 5 and 1 subunits of integrin in B16F10 cells. The cell death observed is probably by apoptosis, after loss of adhesion and might contributes to impair the ability of tumorlung colonization.